Three-Dimensional Volumetric Spatially Angle-Corrected Pixelwise Fetal Flow Volume Measurement - Scholbach, T. M.; Stolle, J.; Scholbach, J. (Ultraschall in der Medizin - European Journal of Ultrasound, 2011)
Purpose: Early attempts to calculate fetal global perfusion used 2 D images. The results were not sufficiently reliable. That‘s why RI measurements are still in use despite the fact that they do not reflect the amount of blood passing through the fetus. We present a novel three-dimensional approach to overcome these limitations. Materials and Methods: In 124 singleton pregnancies between the 23rd and 4st gestational week, a three-dimensional color Doppler sonographic record of the umbilical cord was made, resulting in 281 volume data sets. With dedicated software (PixelFlux) the spatial angle of the umbilical vein was calculated and the true global fetal perfusion was calculated from its horizontal transection as the product of the area of all pixels and the spatial angle-corrected velocity. To validate the PixelFlux technique, phantom flow measurements were carried out. Results: Phantom flow measurements revealed a highly significant correlation of actual flow volumes and those measured by the PixelFlux technique (p < 0.001; rPearson = 0.987 – 0.991) with an even higher interobserver correlation (p < 0.001; rPearson = 0.997). We found a significant correlation of fetal volume flow to gestational age and weight (r = 0.529 at spatial angles below 30° to r = 0.724 at spatial angles below 5°) and a significant influence of the spatial angle on this correlation (p = 0.003; r = – 0.865). Conclusion: Spatial angle-corrected global fetal perfusion measurement improves existing approaches to fetal perfusion evaluation, and is feasible, simple and fast. Thus, it can be recommended to explore the relationship of fetal perfusion and disturbances of fetal development.
Keywords: 3 D ultrasound; fetal volume perfusion; umbilical vein; PixelFlux; spatial angle correction